Registration of vessels in the PRC: diversity of legal regimes - Shuibao, Zhang; Шуйбао, Ч. (Одеса : Гельветика, 2020)
The article is focused on determining the mechanism for the registration of maritime vessels in the PRC. The basis of the study is the international legal framework for the registration of vessels – the United Nations Convention on the Law of the Sea 1982 and the Convention on Conditions for Registration of Ships, 1986. The legislation of mainland China and the special administrative regions of Hong Kong and Macau is considered. The procedures that are applied for entering vessels in their state registers are defined. Positive and negative tendencies of development of registration mechanisms and innovations implemented are outlined. A number of general scientific and specific legal methods were applied during the study. They allowed to develop the author’s vision of possible and desirable changes in the organizational and legal mechanism of registration of vessels in China. The author concludes that there are differences in the procedures for registering ships in mainland China and in special administrative districts. This is a consequence of the prevailing legal tradition in these territories of the western and somewhat more democratic than in mainland China. It is also facilitated by the right to self-identify and regulate most areas of domestic policy, which include shipping. Thus the ship registration rules in PRC can be viewed as three parallel legal orders, that include the Mainland China, the Free Trade Zones and the Hong Kong Special Administrative Region.
Shuibao Z. Registration of vessels in the PRC: diversity of legal regimes / Z. Shuibao // Lex Portus : юрид. наук. журн. / редкол. : С. В. Ківалов (голов. ред. ради), Б. А. Кормич (голов. ред.), Т. В. Аверочкіна (наук. ред., відп. секр.) [та ін.] ; НУ "ОЮА", ГО "МА Святий Миколай". – Одеса : Видавничий дім «Гельветика», 2020. - № 2. – C. 7 - 29.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE; ship registration; international shipping; shipping policy; Hong Kong Special Administrative Region of the People’s Republic of China; Macao Special Administrative Region of the People’s Republic of China; реєстрація суден; міжнародне судноплавство; морська політика; Спеціальний адміністративний район Гонконг КНР; Спеціальний адміністративний район Макао КНР; регистрация судов; международное судоходство; мор- ская политика; Специальный административный район Гонконг КНР; Специальный административный район Макао КНР